A Systematic Review and Meta-Analysis of Moxibustion Treatment for Knee Osteoarthritis - Jang Mi Park; Cham Kyul Lee; Kyung Ho Kim; Eun Jung Kim; Chan Yung Jung; Byung-Kwan Seo; Bon Hyuk Goo; Yong Hyeon Baek; Eun Yong Lee (MEDrang Inc., 2020)
The purpose of this study was to evaluate the evidence supporting the effectiveness of moxibustion treatment for osteoarthritis. There were 9 databases used to retrieve randomized controlled trials (RCTs) that used moxibustion as treatment for osteoarthritis. The quality of methodology for the RCTs was assessed using the Cochrane Risk of Bias tool [Review Manager (RevMan) Version 5.3 Windows, The Nordic Cochrane Centre, Copenhagen, Denmark]. The inclusion criteria for this review was met by 27 RCTs. All studies were conducted in China. A 4-week moxibustion treatment period was the most common. EX-LE4 and SP10 and GB34 acupoints were most frequently selected in the treatment of osteoarthritis. The most commonly used evaluation index was the visual analog scale (VAS). All studies, including a meta-analysis showed that moxibustion treatments were statistically significantly effective at treating knee osteoarthritis. However, well-designed randomized RCTs without a high risk of bias should be designed in the future.